(3SDGd eSYhO GdSLRi ddMGce GdfjSCHhQi Yf LeGYI ef GdNQGSGfjjf heMdge ef GdLQM hGdJYOjds - (3GdMGce GdfjSGHhQjs ((3CHh HcQ Hf Ydi Hf ESeGYjd GdCfUGQi GdHgfSi GdTGaYi s)
(3ChdgG (B:s
(3CNHQfG LeGYI ai cJHge Yf GdMGaX GdabjI CHj GdWGgQ CMeO Hf eMeO Hf CMeO Hf eMeO GdCUHgGfi GdSdai fRjd GdEScfOQjI bO cJHfG Yf LeGYI ef GdNQGSGfjjf heMdge ef GdLQM hGdJYOjd s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3dGJPgH GdCjGe hGddjGdi MJi jedc QLd ef Cgd HjJi hMSHfG Gddg hfYe Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(624(16)) s
Keywords: (3GdMOjK h GdeUWdMs